Keamanan Informasi Data Dalam Pemanfaatan Teknologi Informasi Pada PT Bank Central Asia (BCA) - Edy Soesanto; Nova Astia Ningsih; Lili Khoerunisa; Muhammad Ilham Faturrahman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In this era of very rapid growth of information systems, the security of information is something that must be considered, because if information can be accessed by unauthorized or irresponsible people, then the accuracy of the information will be doubted, it will even become information that is healed. Basically a secure system will protect the data in it such as user assistance (user identification), user authentication (user authentication), user authorization (user authorization). Several possible attacks (Hacking) that can be carried out, such as Intrusion, denial of services, joyrider, vandals, piracy, sniffing, spoofing and others. There are many kinds of threats to information systems, including: data theft, illegal use of systems, illegal data destruction, illegal data modification, system failures, human error (HR-human resources), natural disasters. The purpose of information security is prevent threats to the system and detect and repair damage that occurs to the system.